(3JMaI GdWdGH aj GdYed HGdCSWQdGHs - (3GdUaGQ , CHh GdbGSe GdUaGQCMeO Hf YHO Gddg Hf eMeO GdZGabj,J (B426 (3g` s
(3ChdgG (B:s
(3bGd GdTjN HGH PcQ BdGJ GdCSWQdGH , hGdCSeGA GdhGbYI YdjgG Chd Pdc GdMdbI hJSei GdYdGbI , hgj GdJi jYdb GdCSWQdGH HgG s
(3BNQgG (B:s
(3GdYed YGekG HYO YGe Edi SfI NeS hNeSjf hCQHY eFI ddgLQI hHeG PcQfG jYde JGQjN ehdO GdeSjM Ydjg GdSdGe ef bHd JGQjN GdgLQI GdfHhjI hGddg SHMGfg CYde HGdUhGH Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3jJab ChdgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX hGdYHGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B104s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B256 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B401 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs